Pengaruh Perputaran Persediaan Barang Dagang Terhadap Kebutuhan Modal Kerja - Putri, Dwi Pertiwi (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
In this discussion i will involve two kinds of variables, merchandise inventory variable is the independent variabel or affect of variabel, while the dependent variable is the working capital needs as affected. This study aims to determine the effect of the merchandise inventory turnover of working capital requirements at Serba Usaha Hirup Rukun Cooperation, Sukabumi. The data used in this study is the historical data, obtained from literatureand data obtained from a company’s annual report. Using simple regression analysis with data processing using SPSS 18. From this study, merchandise inventory turnover is always decreasing and determination of working capital requirements tend to decrease each year. From the result of tests performed on this research note that working capital requirements can be affected by merchandise inventory turnover amounted to 95,9% and simultaneously merchandise inventory turnover significantly influence to the working capital needs of the sig level of 0,021is smaller than the probability value of 0,05.